Antibiotic Prophylaxis for Gynecologic Procedures prior to and during the Utilization of Assisted Reproductive Technologies: A Systematic Review. (7th March 2016) - Pereira, Nigel; Hutchinson, Anne P.; Lekovich, Jovana P.; Hobeika, Elie; Elias, Rony T.
Abstract : The use of assisted reproductive technologies (ART) has increased steadily. There has been a corresponding increase in the number of ART-related procedures such as hysterosalpingography (HSG), saline infusion sonography (SIS), hysteroscopy, laparoscopy, oocyte retrieval, and embryo transfer (ET). While performing these procedures, the abdomen, upper vagina, and endocervix are breached, leading to the possibility of seeding pelvic structures with microorganisms. Antibiotic prophylaxis is therefore important to prevent or treat any procedure-related infections. After careful review of the published literature, it is evident that routine antibiotic prophylaxis is generally not recommended for the majority of ART-related procedures. For transcervical procedures such as HSG, SIS, hysteroscopy, ET, and chromotubation, patients at risk for pelvic infections should be screened and treated prior to the procedure. Patients with a history of pelvic inflammatory disease (PID) or dilated fallopian tubes are at high risk for postprocedural infections and should be given antibiotic prophylaxis during procedures such as HSG, SIS, or chromotubation. Antibiotic prophylaxis is recommended prior to oocyte retrieval in patients with a history of endometriosis, PID, ruptured appendicitis, or multiple prior pelvic surgeries.